2009
DOI: 10.7863/jum.2009.28.11.1471
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral and Visceral Blood Flow Velocities in Asphyxiated Term Neonates With Hypoxic-Ischemic Encephalopathy

Abstract: Objective. The purpose of this study was to evaluate changes in the Doppler blood flow velocity (BFV) in the cerebral and visceral arteries in asphyxiated term neonates. Methods. The BFV was measured in 47 asphyxiated and 37 healthy term neonates in the anterior cerebral artery, middle cerebral artery, basilar artery, internal carotid artery, celiac artery (CA), superior mesenteric artery (SMA), and renal artery (RA) up to the age of 60 to 149 days. Results. At the age of 12 to 120 hours after asphyxia, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 35 publications
2
18
0
2
Order By: Relevance
“…At the same time, hypotrophic newborns have increased values of parameters characterizing the resistance of vascular bed in the superior mesenteric artery. The blood flow velocity in the superior mesenteric artery is reduced by birth asphyxia, patent ductus arteriosus, dopamin, dobutamin, indomethacin, caffein and umbilical arterial catheter (12,13). Similar conclusions are reported in the study performed by Martinussen, (1996) (10).…”
Section: Circulation In Eutrophic and Hypotrophic Newbornssupporting
confidence: 82%
“…At the same time, hypotrophic newborns have increased values of parameters characterizing the resistance of vascular bed in the superior mesenteric artery. The blood flow velocity in the superior mesenteric artery is reduced by birth asphyxia, patent ductus arteriosus, dopamin, dobutamin, indomethacin, caffein and umbilical arterial catheter (12,13). Similar conclusions are reported in the study performed by Martinussen, (1996) (10).…”
Section: Circulation In Eutrophic and Hypotrophic Newbornssupporting
confidence: 82%
“…They were clinically stable and in good condition without signs of cardiac or circulatory compromise. Exclusion criteria were the presence of birth asphyxia requiring resuscitation after delivery (Apgar score 7 in the first minute), the presence of congenital anomalies and clinical evidence of any cardiac abnormalities, as these alter visceral blood flow velocities [11,12]. Written informed consent was obtained from each pregnant woman enrolled and from both parents of the infant, thereafter.…”
Section: Subjectsmentioning
confidence: 99%
“…In addition to the effects of vasoactive metabolites, other mechanisms, including neurogenic vasodilation, have been proposed (14). Previous studies in infants focused mainly on changes in CBF velocity (CBFV) measured using Doppler ultrasonography in infants with neonatal encephalopathy (NE) (15)(16)(17). Higher mean CBFV values have been found during the first days after asphyxia in infants with severe NE as compared with a control group of infants with mild to moderate NE and healthy infants, the maximum values of CBFV being seen at 36-72 h after birth (16,17).…”
Section: Carotid Blood Flow and Time After The Infarctionmentioning
confidence: 99%
“…Previous studies in infants focused mainly on changes in CBF velocity (CBFV) measured using Doppler ultrasonography in infants with neonatal encephalopathy (NE) (15)(16)(17). Higher mean CBFV values have been found during the first days after asphyxia in infants with severe NE as compared with a control group of infants with mild to moderate NE and healthy infants, the maximum values of CBFV being seen at 36-72 h after birth (16,17). More recently, using perfusionweighted imaging, Wintermark et al reported observing initial hypoperfusion followed by hyperperfusion on days 2 and 3 in infants who develop brain injury after NE (18).…”
Section: Carotid Blood Flow and Time After The Infarctionmentioning
confidence: 99%